Acquisition of motor abilities up to independent walking in very low birth weight preterm infants - Volpi, Sandra C. P. [UNESP]; Rugolo, Ligia M. S. S. [UNESP]; Peraçoli, José Carlos [UNESP]; Corrente, Jose Eduardo [UNESP] (Sociedade Brasileira de Pediatria, 2010)
Objective: To determine chronological and corrected ages at acquisition of motor abilities up to independent walking in very low birth weight preterms and to determine up to what point it is necessary to use corrected age.Methods: This was a longitudinal study of preterms with birth weight < 1,500 g and gestational age <= 34 weeks, free from neurosensory sequelae, selected at the high-risk infants follow-up clinic at the Hospital das Clinicas, Faculdade de Medicine de Botucatu, Universidade Estadual Paulista (UNESP) in Botucatu, Brazil, between 1998 to 2003, and assessed every 2 months until acquisition of independent walking.Results: Nine percent of the 155 preterms recruited were excluded from the study, leaving a total of 143 patients. The mean gestational age was 30 +/- 2 weeks, birth weight was 1,130 +/- 222 g, 59% were female and 44% were small for gestational age. Preterms achieved head control in their second month, could sit independent at 7 months and walked at 12.8 months' corrected age, corresponding to the 4th, 9th and 15th months of chronological age. There were significant differences between chronological age and corrected age for all motor abilities. Preterms who were small for their gestational age acquired motor abilities later, but still within expected limits.Conclusions: Very low birth weight preterms, free from neurosensory disorders, acquired their motor abilities within the ranges expected for their corrected ages. Corrected age should be used until independent walking is achieved.
Aquisição de habilidades motoras até a marcha independente em prematuros de muito baixo peso